Salient bactericidal activity of blood serum protein complement against Escherichia coli and Shigella flexneri in urban and slum population of Bangladesh : a comparative study - Binta Mosharraf, Fahareen; Karim, Mehnaz; Mohammad Shafiqul Kalam, Iftekhar; Mirza, Nahreen (International Journal of Engineering and Technology, 2018)
Studies over the years evinced that complement participates in nearly every step of the immune reaction justifiably deserve a central position in the immunological research. The last several years have been observed as an enormous expansion in our understanding of the details of complement biochemistry and in our appreciation of the role of complement proteins in biological phenomena. This observation particularly calls for the in vitro examination of complement proteins activity, derived from blood serum of a defined group of urban and slum people against E. coli and Shigella flexneri, which are a major cause of large scale epidemics and thousands of sporadic cases of gastrointestinal illness. In this exertion we attempt to make a comparative analysis on complement mediated killing of clinical isolates of E. coli and S. flexneri derived by serum collected from urban and slum population. Hence the slum population showed more effective complement mediated killing in comparison to urban population. Moreover complement plays a central role in the installation of the adaptive innate immune response in clearence of E. coli and S. flexneri in vitro from both population which is statistically significant.Â Â Â